Moradia e idoso: um estudo sobre o lugar de envelhecer - Grezele, Gabriely (Universidade Federal de São Carlos, 2022)
The place of residence directly reflects on active and healthy old age. It is known that the aging process is accompanied by a series of biopsychosocial issues influenced by several factors. Adequate housing can be a facilitator in the process. However, the elderly population increasingly depends on State initiatives to obtain access to adequate housing, and therefore, dignified conditions in old age, reflecting on functional capacity. In this scenario, specific public policies that do not take into account aspects related to health and well being can impact daily activities of daily living and relationships with the place. In this sense, there is a need for studies that investigate housing characteristics and the profile of the elderly in each location, in order to deepen the knowledge regarding the socio-spatial insertion of the resident. It is understood that care policies for the elderly can promote active and healthy aging, regardless of the level of socioeconomic development, enabling the maintenance of functional capacity in a safe environment, encouraging participation in the community. Therefore, the objective of this study was to analyze the housing conditions and the functional capacity of elderly residents of the CECAP neighborhood in Araraquara-SP. It is a transversal, exploratory and descriptive research, based on the quantitative-qualitative method of investigation. The research participants were elderly people registered in the public health facilities that served the neighborhood. Interviews were conducted with semi-structured questions, and the Brazilian Oars Multidimensional Functional Assessment Questionnaire (BOMFAQ) was used to assess functional capacity. The results indicated that the interviewees do not have severe commitment to the performance of daily activities, but they have greater difficulties in the IADL, which are related to health conditions and not directly with the neighborhood. Regarding the participants' perception of housing, it was noted that the feeling of well-being, possession, living conditions and the understanding that there is an offer of product and service structures within the neighborhood, are important aspects that reflect on the quality of housing. of what is lived and the understanding that their housing meets their needs, reflecting on the feeling of belonging, integration and conditions to enjoy the space independently, actively and with dignity in old age.
Housing and the elderly: a study on the place of aging
Keywords: Capacidade funcional; Envelhecimento populacional; Moradia adequada; Planejamento urbano; Políticas de atenção ao idoso; Functional capacity; Population-ageing; Adequate housing; Urban planning; Elderly care policies; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL